Leveraging Green Finance and Digitalization for enhancement of SMEs’ performance in Nepal: Mediating Role of Sustainable Business Practices - Shrestha, Romy; Shrestha, Adrija; Tiwari, Mohit (New Perspective: Journal of Business and Economics, 2025)
This study examines the effect of green finance and digitalization on the business performance of SMEs, with a particular focus on the mediating role of sustainable business practices in the relationship of green finance and business performances and digitalization and business performances. A quantitative research method has been employed in this study where primary data with a sample size of 135 was collected from field surveys done inside the Kathmandu valley through a structured questionnaire developed using a 5-point Likert scale. The collected data were coded into SPSS for descriptive and inferential analysis, using Regression Analysis and the Baron Kenny mediation analysis to assess the relationship between the variables. The findings indicated that both green finance and digitalization positively impact the business performance of SMEs. Sustainable business practices partially mediate the relationship between green finance and performance, but no such mediating effect was found for digitalization. These findings underscore the importance of aligning green finance initiatives with sustainable business practices to achieve improved performance outcomes among SMEs.